(untitled) (Cuadernos de Extensión Universitaria de la UNLPam, 2021)
University extension always involves bringing into play at least two central elements: synergy and multiplicity of voices. Therefore, this article has the objective of critically socializing the presence of our “partners” in the co-construction of knowledge, collecting the different voices during various extension projects promoted by the Educationand Society Program: towards greater educational inclusion dependent on the Extension Secretariat Social and Cultural of the UNL. We will divide this article into three sections, related to projects anchored in the Program. We refer to university social volunteering practices, Experimental Sciences teaching and learning projects and finally to rural education projects. Returning to them highlighting the actors’ glances allowsus to rethink and adjust our own view.